Making multiple babies : anticipatory regimes of assisted reproduction - Wu, Chia-Ling, 1966- (Fertility, reproduction and sexuality ;, 2023)
"Human beings have been producing more twins, triplets, and quadruplets than ever before, due to the expansion of medically assisted conception. This book analyzes the anticipatory regimes of making multiple babies. With archival documents, participant observation, in-depth interviews, and registry data, this book traces the global and local governance of the assisted reproductive technologies (ARTs) used to tackle multiple pregnancy since the 1970s, highlighting the early promotion of single embryo transfer in Belgium and Japan and the making of the world's most lenient guidelines in Taiwan"--